EXPLORING BIDARA LEAVES AS A SUSTAINABLE CORROSION INHIBITOR FOR AISI 1045 STEEL IN 3,5% NACL SOLUTION - Magga, Ramang; Tence, Tence; Zuchry, Muhammad; Marsan, Kennedy; Kali, Agustinus (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
This research investigated the efficacy of bidara leaf extract (BLE) as a natural corrosion inhibitor for AISI 1045 steel in a 3.5% NaCl solution. Different concentrations of BLE (0%, 0.05%, 0.10%, and 0.15%) were examined by the immersion method, potentiodynamic polarization (PDP), and electrochemical impedance spectroscopy (EIS) to assess the corrosion rate and inhibition efficiency. The findings indicated that the minimal corrosion rate was seen at 0.15% BLE concentration. PDP study demonstrated a notable reduction in current density (icorr) as BLE concentration increased, signifying its efficacy in corrosion inhibition. The test findings indicated an elevation in charge transfer resistance, corroborating the establishment of a stable protective layer on the steel surface. SEM-EDX research further confirmed the existence of negligible surface damage and the adsorption of organic inhibitor layers. The active chemicals in BLE facilitated the passivation process, diminishing oxidation-reduction processes and decelerating the corrosion rate. The findings affirm that bidara leaf extract is a viable eco-friendly alternative as a natural inhibitor to mitigate corrosion and offer sustainable protection for low-carbon steel in NaCl.